Sikap dan Perilaku Komunitas Warga mengenai Maraknya Pedagang Kaki Lima - Yulianita, Neni (FIkom Unisba, 2005)
Streetmerchant, famously known in Indonesia as Pedagang Kaki Lima (PKL) raise some problems for the city every year. The city government has tried to locate them in some areas, the amount of PKL has never decreased. From the year of 1997 to 2000, the amount of PKL has increased 56.3%/year. It means, from around 3.000 PKL in 1997, the amount of PKL has hit a number of 16.880 due to the worsening of economic conditions. This research aimed to study problems concerning PKL and interactions among PKL, city government, and community itself. It is found that opinions of community members toward PKL are varying: some feels uncomfortable, another think that it’s not their problems, on the other hand, people admit that they need PKL to supply materials for them.